PMO-097 Surgery for pancreatic cancer without preoperative biliary drainage: fiction in reality?. (28th May 2012) - Daker, C; van Someren, N; Besherdas, K
Abstract : Introduction: A recent article published in the New England Journal of Medicine describes decreased complication rate in patients who have not had preoperative biliary drainage of their obstructive jaundice caused by their pancreatic mass. Unfortunately our perception is such that the reality of early surgery without a bridging stent hangs in the realms of fantasy. Our aims were to analyse the outcome of patients diagnosed to have pancreatic cancer in clinical practice in North London. Methods: In this duel centre retrospective study, a years worth of pancreatic cancer diagnoses was compiled using the North London Cancer Network Multi-disciplinary team meeting data base. The patients records were then searched gathering information on their dates of diagnosis; referral to our hepatobiliary surgeons at a local tertiary referral centre; whether they had a pre-operative stent; the date of their surgery (if they survived long enough to have it) and they're ultimate outcome. Results: 68 patients within our sector received a diagnosis (histological/endoscopic/radiological) of pancreatic cancer over the course of 1 year (May 2010–May 2011). Of this cohort 20 (29.4%) were referred for surgical opinion. During the lag between diagnosis and surgical review, 9 (45%) patients received endoscopic biliary drainage and stent insertion (all were 1st pass). The total number to ultimately receive their Whipple's was 5 (25%). In four patients in whom surgery was felt to be an option, aggressive disease and complications leading to a lengthy in patient stay at the point of diagnosis meant that the physical condition of the patient had deteriorated to the point where they were no longer fit for surgery/inoperable. Only one patient proceeded straight to operation without prior stenting. Two patients had their operations privately. Unfortunately details of any post operative complications are not available. Conclusion: Our experiences of pancreatic cancer is that at the point of diagnosis most cancers were inoperable 48 of 68 (70%). Within our study period only 5 of 68 (7%) patients had surgery for pancreatic cancer. The majority of patients even when initially considered for surgery (75%) do not end up having a resection. When patients are referred with symptoms of obstructive jaundice, knowing that the majority will not undergo surgery and also knowing in clinical practice that it is difficult to get surgical resection within 10 days of diagnosis, the humane thing to do instinctively is to stent and achieve biliary drainage. Achieving biliary drainage helps in improving the patients symptom profile and additionally allows chemotherapeutic options in those whose jaundice resolves. Competing interests: None declared.